Resiliency as a factor protecting youths from risky behaviour: Moderating effects of gender and sport. Issue 2 (17th February 2016) - Lipowski, Mariusz; Lipowska, Małgorzata; Jochimek, Magdalena; Krokosz, Daniel
Abstract: We hypothesised that resiliency may protect adolescents against risky behaviours, and that both the practicing of sports, and gender are moderating variables in relationships between resiliency and risky behaviours. The study included 18-year-old pupils from a selection of secondary schools ( n = 556). A total of 188 individuals practiced competitive sports and the remaining 368 participants were non-athletes. The participants were examined with the Resiliency Assessment Scale for Children and Adolescents (SPP-18) and with a survey containing questions and statements related to high-risk "experiments with adulthood". Adolescent athletes showed higher levels of resiliency than their peers. The power of the "Determination and Persistence in Action" effect on "Alcohol" scale differed significantly between male athletes and male non-athletes. Only in the athletes groups were higher scores on this scale reflected by lower values on the "Drugs" scale. Moreover, it is possible to observe differences in undertaking risky behaviour between male and female athletes. The analysis of risky sexual behaviour suggests that sport is a risk factor for men, and a protective factor for women. These data suggest that consistent prophylactic and psycho-educative activities, with a special attention to differences between genders, should be provided to all the adolescents, irrespective of their sport performance levels.